Epidemiologic Modeling of Cervical Dysplasia with Molecular and Cytopathological Markers - Scheurer, Michael E. (2007)
OBJECTIVES: Conventional cervical screening is insufficient at identifying patients who are likely to progress from cervical dysplasia to carcinoma. Traditional epidemiologic studies have identified potential factors to aid in the discrimination between those lesions likely to progress from those likely to regress; however, there is still much to be learned. To examine the role of traditional epidemiologic factors in conjunction with molecular markers of human papillomavirus activity, we studied a group of women attending colposcopy clinics in Houston, TX and Vancouver, BC between October 2000 and July 2003. METHODS: Quantitative real-time PCR was used to measure mRNA expression of the human papillomavirus E7 gene, and quantitative cytology was used to gather information about the DNA index and chromatin features of the cells from these women. Logistic regression was used to establish predictor variables for histologic grade based on the epidemiologic risk factors and the molecular markers. RESULTS: The most predictive factors were mRNA level, DNA index, parity, and age. The ROC curve for the individual logits indicated excellent discrimination. CONCLUSION: In accordance with other authors, these results suggest that molecular markers of the malignant process should be included in analyses looking to predict the progression potential of cervical lesions.